PENGARUH PERTUMBUHAN EKONOMI TERHADAP KESEMPATAN KERJA DI PROVINSI SULAWESI TENGGARA - Muhammad Nur Afiat (Universitas Muhammadiyah Kendari, 2017)
This study was conducted with the aim to determine the effect of Economic Growth Rate on Employment Opportunities in Southeast Sulawesi Province 2000-2015. This research is a type of Quantitative research using secondary data in the form of time series data, ie from 2000-2015. Data source was obtained from Central Bureau of Statistics (BPS) and Bank Indonesia of Southeast Sulawesi Province. This study also uses multiple linear regression analysis tools with ordinary least square method (OLS) and then processed with application Eviews 8.0. The results of the study show that Economic Growth has a significant influence on Employment Opportunities in Southeast Sulawesi Province 2000-2015.